The information needs of cancer patients in the Pretoria and Witwatersrand area - H. A. McLoughlin; B. L. Oosthuizen (AOSIS, 1996)
More than 48 500 South Africans annually are confronted with the diagnosis of cancer. (Sitas, 1994) Judging from the literature it would seem that the acquisition of information about the various aspects of their disease is a very important coping mechanism for the cancer patient. Various studies concerning the information needs of cancer patients have been published in the USA, the UK and Australia, Similar studies have not yet been published in South Africa.